A Study on Finding Ways to Efficiently Learn Theory and Practice in Nursing and Clinical Practice Education -Focus Interviews with Nursing Students and Clinical Instructor- - Lee, Do-Young (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Since professional nursing is a practice-oriented study applied in the nursing field based on theoretical nursing knowledge, the clinical practice focuses on the subjects in the nursing curriculum. Methods/Statistical analysis: Nursing practice education should be integrated with theory and practice, and applied to the subjects to improve their problem-solving ability and to provide the subjects with a holistic approach. Therefore, this study endeavors to analyze the focus of nursing education through clinical interviews with nursing students and clinical leaders in order to achieve effective clinical practice.Findings: The results of the study are based on analysis of focus interviews between nursing students and clinical instructors. In the case of nursing school students: 'demand of consistent education on techniques', 'experience of importance of communication education', 'consciousness of the necessity of nursing techniques reflecting reality', and 'demand of practical nursing record education’. In the case of clinical instructors, it found out three themes. : ‘Consistent Recognition of Needs for Reinforcement of Education for Communication’,‘Reinforcement of Field-oriented Practice Class’and‘Diverse Experience and Improvement of Adaptability through Scenario’. The results of this study are expected to be used as basic data for solving practical problems such as maladjustment of practice and turnover of nurses.Improvements/Applications: Although it is difficult to integrate theory and practice in nursing science, I hope that innovation in practical education will be based on the results of this study.